Case report:18F-2-deoxy-2-fluoro-D-glucose positron emission tomography/computed tomography image findings of a dog with gossypiboma - Kim, Su-Hyeon; Lee, Sungin (Frontiers in Veterinary Science, 2023)
A 13-year-old, spayed, female mixed breed dog that had previously undergone mastectomy and ovariohysterectomy at our institution was referred to the nuclear medicine department for metastasis evaluation following surgery. 18F-deoxy-2-D-glucose positron emission tomography/computed tomography (18F-FDG PET-CT) was performed and a soft-tissue mass was observed in the abdominal cavity. The characteristics of the abdominal mass were assessed and screening for metastasis was done with follow-up 18F-FDG PET scans. Uptake of 18F-deoxy-2-D-glucose was higher in the peripheral region and lower in the center of the abdominal mass. Exploratory laparotomy was performed, and the removed abdominal mass was consistent with a gossypiboma, which is a retained surgical sponge composed of non-absorbable material with cotton matrix. This case report describes the characteristics of 18F-FDG PET-CT imaging in a dog with an abdominal gossypiboma, which has not been reported in the veterinary literature before.